Feeding cluster preferences in four genera of Lories and Lorikeets (Loriinae) that should be considered in the diet of nectarivorous psittacine species in captivity. Issue 1 (8th November 2018) - Cabana, Francis; Lee, Jessica G.
Abstract: Lories and lorikeets are popular birds in the pet bird trade, captured from the wild and exported worldwide. Their captive propagation has not been so successful for many species due to health issues, low breeding success and reduced longevity. As a result, uptake from the wild is currently the only way to meet the market's demand. Field studies on Asian species of loris and lorikeets are limited; therefore, dietary recommendations are based on the well‐studied Australian species such as the rainbow lorikeet ( Trichoglossus moluccanus ). We aimed to provide an ad libitum diet to diverse Loriinae species at Jurong Bird Park (Singapore) which allowed for them to select between a low and moderate protein diet to compare their nutrient and energy intake with other Loriinae species . We measured the following variables: daily dry matter (DM) intake, nectar‐to‐fruit energy intake ratio (NF ratio), metabolisable energy (ME), protein and non‐protein energy (NPE)‐to‐protein energy (PE) ratio intake (all by kg metabolic body weight MBW, kg 0.75 ) for 36 pairs over a 1‐month period. A Kruskal–Wallis test revealed every genus had significantly different intakes of DM, NF ratio, NPE‐to‐PE ratio, ME and protein than each other. Post hoc Mann–Whitney U tests confirmed that the majority of variables were ingested in different amounts for each genus except for NF ratio, NPE/PE ratio which Lorius spp. are not different to Charmosyna sp. or Trichoglossus spp. and protein intake of Eos spp. does not differ from Trichoglossus spp. Our conclusion is that no species should be used as a model for a species from another genus of Loriinae; future studies should be species‐specific for each genus to increase captive propagation success.